2019
DOI: 10.1136/bmjsrh-2018-200278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self-administration of misoprostol for early medical abortion: a prospective observational cohort study

Abstract: IntroductionIn October 2017, Scotland legalised the home use of misoprostol for the purpose of early medical abortion (EMA). Women up to 9+6 weeks’ gestation can now self-administer the drug at home, 24–48 hours after receiving mifepristone in the clinic.ObjectiveTo evaluate the impact of this change on the uptake and success rate of EMA, and on the provision of effective contraception on discharge.MethodsA prospective observational study was conducted to compare the outcomes of two cohorts of women in the 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
0
16
2
Order By: Relevance
“…In our study, rates of telephone contact to the service for a concern related to the abortion were similar to our previous studies. 14 15 However, we did observe a higher proportion of women requiring a post-abortion clinic attendance (8.4%) compared with our former service model with routine pre-abortion ultrasound and clinic-administered mifepristone with misoprostol at home (2.7%). 14 The majority of the post-abortion clinic visits were to exclude continuing pregnancy following a positive or invalid LSPT.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In our study, rates of telephone contact to the service for a concern related to the abortion were similar to our previous studies. 14 15 However, we did observe a higher proportion of women requiring a post-abortion clinic attendance (8.4%) compared with our former service model with routine pre-abortion ultrasound and clinic-administered mifepristone with misoprostol at home (2.7%). 14 The majority of the post-abortion clinic visits were to exclude continuing pregnancy following a positive or invalid LSPT.…”
Section: Discussioncontrasting
confidence: 70%
“…These findings are similar to previous cohort studies from this service of women who took misoprostol at home having had routine ultrasound and mifepristone in clinic. 14 15 17 Women reported high levels of preparedness to use the medications in their own homes. Indeed, acceptability of care was high, and the majority of women expressed a preference for choosing this model of care again in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rich data generated has enabled further exploration of women's experiences, and areas as yet unexplored in the literature. All women were recruited from one NHS Lothian clinic where 72% of women have EMAH-SaM and where, at the time of fieldwork, this had been an option for over a year [6]. The findings may not be reflective of women's experiences where the service is newer.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2017 -2019, legislation was introduced in the UK that approved the home as a place for self-administration of misoprostol for early medical abortion (≤69 days gestation). While research has shown that early medical abortion at home is as safe as in a clinical setting [6], UK women's experiences in the context of this change have not yet been investigated. This qualitative research explores the experiences of women choosing EMAH-SaM, in one region of Scotland, UK.…”
Section: Introductionmentioning
confidence: 99%